KAWASAN AGROWISATA JERUK DI NAGARI KOTO TINGGI KECAMATAN BASO KABUPATEN AGAM - Recha Ardianti; Ahyuni Ahyuni (JURNAL BUANA, 2020)
This study aims to: 1) determine the physical and cultural potential associated with the development of the Citrus Agro Tourism Area in Nagari Koto Tinggi, Baso District, Agam Regency and 2) determine the feasibility of developing the Citrus Agro Tourism Area in Nagari Koto Tinggi, Baso District, Agam Regency This type of research is a descriptive study with a quantitative approach. The method used in this study is the scoring method or weighting for each Agro-tourism eligibility criteria. The analysis used to analyze the physical potential is seen from the suitability of citrus land, namely overlay analysis and matcing system (matching) between land quality / characteristics of land suitability with the requirements for growing citrus plants.. Based on the results of the study, it can be seen that: 1) Analysis of physical potential seen from the suitability of citrus plant land, shows the suitability of citrus plant land in Nagari Koto Tinggi Baso District consists of three classes, namely S1 (very appropriate) with an area of 805.23 hectares, S2 (S2 quite suitable) with an area of 883.71 hectares, and class N (not suitable) with an area of 176.73 hectares. The land suitability class of citrus plants in Nagari Koto Tinggi Baso District is more dominant in the land suitability class S2 (quite appropriate). As for the cultural potential that exists in Nagari Koto Tinggi, especially in Jorong Koto Gadang, it emphasizes the Minangkabau traditional culture in general, such as pencak silat, galombang dance, bansi, and the Gadang House with carvings still preserved. 2) And the overall results can be concluded that Nagari Koto Tinggi, Baso Subdistrict, Agam Regency is feasible to be developed into the Citrus Agro Tourism Area, because it is also supported by physical and cultural potentials. The physical potential that exists at the moment in Nagari Koto Tinggi Baso District from citrus plants that are still producing about 35% with an area of ​​70 hectares. As for the cultural potential that is in Nagari Koto Tinggi that is characteristic is the Rumah Gadang with the Maharam Elephant Gadang type house.